Corruption and Economic Growth: The Case of EMCCA - Ondo, Assoumou (Scientific Research, 2017)
This article analyzes the relationship between corruption and economic growth in the countries of the Economic and Monetary Community of Central Africa (EMCCA). To our knowledge, there are no works dealing with the direct relations between the two variables in such a framework. For this purpose, we use panel data econometrics to show that over the period 2005 to 2015, corruption has favored economic growth in the CEMAC member countries by “grazing” the administrative burdens that impede access basic public services (water, electricity, public hospitals and public schools), the creation and development of private enterprises.
Keywords: Corruption; Endogenous Growth; Static Panel